P. 1
Set Theory Lecture Notes

Set Theory Lecture Notes

|Views: 1,958|Likes:
Published by yusuf

More info:

Published by: yusuf on Jan 17, 2010
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

11/22/2012

pdf

text

original

“Induction” is a method of proving statements about natural numbers. Suppose
φ(x) is a statement about the natural number x, and that we want to prove the
statement “φ(x) for all x∈N”. We can proceed as follows:
1) We first show that the statement φ(x) holds for n = 0, i.e. we prove φ(0).
2) Next, we show that whenever φ(n) holds for some natural number n, then
φ(n+1) holds; in other words, we show that if φ(n) holds then φ(n+ 1) holds.
If we can successfully do these two steps, then φ(x) will hold for all x ∈ N.
Because, by the first step, we will know that φ(0) holds. Since φ(0) holds, by
the second step (take n = 0) φ(1) will hold. Now that we know φ(1) holds, by
the second step (take n = 1) φ(2) will hold. Now that we know φ(2) holds, by
the second step (take n = 2) φ(3) will hold, etc. So φ(x) will hold for all x∈N,
as we can check one by one all numbers1
.

Example. As an exercise, let us prove that for all x∈N, 0+1+2+...+x =
x(x+ 1)/2. We let φ(x) denote “0 + 1 + 2 +...+x = x(x+ 1)/2”.
Step 1. φ(0) holds. Indeed, φ(0) says that the sum of natural numbers
from 0 to 0 is 0(0 + 1)/2, i.e. is 0. This is of course true.
Step 2. If φ(n) holds then φ(n + 1) holds. Assume φ(n) holds, i.e.
assume that 0 + 1 + 2 + ... + n = n(n + 1)/2. Under this assumption, we will
show that 0 + 1 + 2 + ... + n + (n + 1) = (n + 1)(n + 2)/2 (just replace x by
n+1 in φ(x)): 0+1+2+...+n+(n+1) = (0+1+2+...+n)+(n+1) =

n(n+1)/2+(n+1) = (n+1)(n+2)/2. (Here the second equality follows from
the assumption that φ(n) holds. The rest are purely algebraic).
Therefore φ(x) holds for all x∈N.

Definition by Induction. We can also define functions or sets by induction.
For example, let us consider the function f :N−→N by the rule f(0) = 1 and

1

If this last statement sounds strange to you, then you are a pretty good mathematician.
What we have here is not a precise mathematical proof, but only a heuristic argument why
φ(x) should hold for all x ∈ N. In the next part, we will prove that steps (1) and (2), do
indeed proof “φ(x) for all x ∈ N”.

57

58

CHAPTER 5. INDUCTION

f(n+ 1) = 2f(n) for all n∈N. Then,

f(0) = 1

f(1) = 2f(0) = 2

f(2) = 2f(1) = 2×2 = 4

f(3) = 2f(2) = 2×4 = 8

More generally, one sees that f(n) = 2n
.
Let us consider the following function defined by induction: g(0) = 3, g(1) =
2, g(2) = 1 and g(n+ 1) = g(g(n)) for all n≥2. Then

g(0) = 3

g(1) = 2

g(2) = 1

g(3) = g(g(2)) = g(1) = 2

g(4) = g(g(3)) = g(2) = 1

g(5) = g(g(4)) = g(1) = 2

g(6) = g(g(5)) = g(2) = 1

On the other hand the following attempt of definition by induction fails:
h(0) = 0, h(1) = 2, h(2) = 3 and h(n+ 1) = h(h(n)) for all n≥2, because

h(3) = h(h(2)) = h(3) = h(h(2)) = h(3) = ...

We can use induction to define addition from the successor function S :
N−→N given by S(n) = n+ 1 as follows: n+ 0 = n for all n∈N and

n+ (m+ 1) = (n+m) + 1

for all n, m∈N.

We can use + to define multiplication: n×0 = n for all n∈N and

n×(m+ 1) = n×m+n

for all n, m∈N.
We can use × to define exponentiation: n0

= 1 if n = 0, 0m

= 0 for all

m = 0 and

nm+1

= nm

×n

for all n, m∈N.
We also define factorial as follows: 0! = 1 and

(n+ 1)! = n!×(n+ 1)

for all n∈N.

n Choose k. For n, k ∈N and k ≤n, define
n
k

= n!

k!(n−k)!.

A priory

n
k

= n!

k!(n−k)! ∈Q. We will see in fact that it is in N.

59

Exercises.

i. Show that for any natural number n and for any real number x∈[0,1],

(1−x)n

≤1−nx+ n(n−1)

2 x2

.

ii. Show that n! > 2n

for all n large enough.

iii. Show that (x−1)n

≥xn

−nxn−1

for all x > 1.

iv. Show that if 0 < x < 1 and n > 0 is a natural number, then (1−x)n

1−nx+ n(n−1)

2 x2

.

v. Show that for any n∈N\{0}, 13

+ 23

+...+n3

= (1 + 2 +...+n)2
.

vi. Show that for any n∈N\{0}, 14

+ 24

+...+n4

= n(n+1)(6n3

+9n2

+n−1)

30

.

vii. Given a set X, define ℘n

(X) as follows by induction on n: ℘0

(X) = X

and ℘n+1

(X) = ℘(℘n

(X)). Show that ℘(℘n

(X)) = ℘n

(℘(X)) for all sets

X and all natural numbers n.

viii. Given a set X and a natural number n, define ℘n

(X) as follows by induc-

tion on n: ℘0

(X) = X and ℘n+1

(X) = ℘(℘n

(X)). Find all n such that

for any set X, {{∅},{{X}}}∈℘n

(X).

ix. Show that

n
k

=

n
n−k

.

x. Show that

n

0

=

n
n

= 1.

xi. Show that

n

1

= n.

xii. Show that

n+ 1
k + 1

=

n
k

+

n
k + 1

.

xiii. Deduce that

n
k

N. (Hint: By induction on n).

xiv. Show that for n ∈ N and 0 ≤ k ≤ n, a set with n elements has

n
k

subsets with k elements.

xv. Show that for n ∈ N and k ∈ N with k ≤ n, a set with n elements has

n
k

subsets with k elements.

60

CHAPTER 5. INDUCTION

xvi. Show that for x, y ∈R and n∈N,

(x+y)n

=

n
k=0

n
k

xk

yn−k
.

(Hint: By induction on n).

xvii. Show that n

k=0

n
k

= 2n
.

xviii. Show that n

k=0(−1)k

n
k

= 0.

xix. Compute (x+y +z)3

in terms of x, y and z.

xx. Compute (x+y +z)4

in terms of x, y and z.

xxi. Show that for x > 1 and n∈N, (x−1)n

≥xn

−nxn−1

.

xxii. Show that for x < 1, (1−x)n

≥1−nx.

xxiii. Show that for n∈N\{0}, (1 + 1

n)n

≤(1 + 1

n+1)n+1

.

xxiv. Find and prove (by induction) formulas for the sums

3

12

·22 + 5
22

·32 +···+ 2n+ 1
n2

·(n+ 1)2

and

1 + 9 + 25 +···+ (2n+ 1)2
.

xxv. Prove by induction that for all real numbers a and b and natural number

n,

(an

+an−1

b+an−2

b2

+···abn−1

+bn

)(a−b) = an+1

−bn+1
.

Chapter 6

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->